2019
DOI: 10.1021/acs.jpcb.9b10250
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electronic Polarization on the Spectral Density

Abstract: Accurate spectral densities are necessary for computing realistic exciton dynamics and nonlinear optical spectra of chromophores in condensedphase environments, including multichromophore pigment−protein systems. However, due to the significant computational cost of computing spectral densities from first principles, requiring many thousands of excited-state calculations, most simulations of realistic systems rely on treating the environment as fixed-point charges. Here, using a number of representative system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(79 citation statements)
references
References 94 publications
3
62
0
Order By: Relevance
“…48,60,[95][96][97][98] Snapshots are extracted every 2 fs, and TDDFT vertical excitation energies are computed using the Tamm-Dancoff approximation, where all solvent molecules within 6Å of the chromophore are treated fully quantum mechanically to capture polarization effects from first principles. 28,31,34,35,38,39,41,42,46 All other surrounding water molecules are included in the excited state calculation as classical point charges. Although this QM treatment of the solvent when computing the vertical excitation energies leads to a small Hamiltonian mismatch between dynamics and excited state calculations, we have found in previous studies that this polarization can rather dramatically affect the spectral densities and we choose here to include the environment at the QM level.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…48,60,[95][96][97][98] Snapshots are extracted every 2 fs, and TDDFT vertical excitation energies are computed using the Tamm-Dancoff approximation, where all solvent molecules within 6Å of the chromophore are treated fully quantum mechanically to capture polarization effects from first principles. 28,31,34,35,38,39,41,42,46 All other surrounding water molecules are included in the excited state calculation as classical point charges. Although this QM treatment of the solvent when computing the vertical excitation energies leads to a small Hamiltonian mismatch between dynamics and excited state calculations, we have found in previous studies that this polarization can rather dramatically affect the spectral densities and we choose here to include the environment at the QM level.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Truncation at second order maps the system dynamics onto a fictitious bath of linearly coupled harmonic oscillators, for which linear and nonlinear spectroscopy signals can be computed analytically. 47 The electronic-vibrational coupling in the system is then fully defined by the autocorrelation function of energy gap fluctuations, which can be efficiently obtained in complex condensed phase systems by computing vertical excitation energies along molecular dynamics (MD) trajectories [23][24][25][26][27]46,[48][49][50] and using quantum correction factors (QCF) 49,[51][52][53] to account for nuclear quantum effects.…”
Section: Introductionmentioning
confidence: 99%
“…[51][52][53] Classical correlation functions are generally much easier to compute than their quantum counterparts and can, for example, be constructed by calculating vertical excitation energies along an MD trajectory. [23][24][25][26][27]46,[48][49][50] Although the choice of QCF is not unique, 49,52 a commonly used approximation for the energy-gap autocorrelation function C {2} δU (t) is the harmonic QCF, where…”
Section: Quantum Correction Factors (Qcfs)mentioning
confidence: 99%
“…[43][44][45] We have recently shown that the electronic-vibrational coupling strength of fast chromophore degrees of freedom to an electronic excitation can also be heavily influenced by the quantum mechanical treatment of the environment. 46 An appealing way to account for the effect of the complex environment and the coupling of nuclear motion to the optical excitation in linear and nonlinear spectroscopy is the cumulant approach, 47 where the response function of the system is expressed in terms of a cumulant expansion of the energy gap operator between the electronic ground and excited state. If the energy gap fluctuations obey Gaussian statistics, as they do for harmonic ground and excited state potential energy surfaces (PESs) of the same curvature, then the cumulant expansion is exact at second order.…”
Section: Introductionmentioning
confidence: 99%
“…Truncation at second order maps the system dynamics onto a fictitious bath of linearly coupled harmonic oscillators, for which linear and nonlinear spectroscopy signals can be computed analytically. 47 The electronic-vibrational coupling in the system is then fully defined by the autocorrelation function of energy gap fluctuations, which can be efficiently obtained in complex condensed phase systems by computing vertical excitation energies along molecular dynamics (MD) trajectories [23][24][25][26][27]46,[48][49][50] and using quantum correction factors (QCF) 49,[51][52][53] to account for nuclear quantum effects.…”
Section: Introductionmentioning
confidence: 99%